Treatment of epistaxis in hereditary hemorrhagic telangiectasia with tranexamic acid: a double-blind placebo-controlled cross-over phase IIIB study - Geisthoff, Urban Wilhelm; Seyfert, Ulrich T.; Kübler, Marcus; Bieg, Birgitt; Plinkert, Peter K.; König, Jochem (Thrombosis research, 2014)
Introduction - Epistaxis is the most frequent manifestation in hereditary hemorrhagic telangiectasia, in which no optimal treatment exists. It can lead to severe anemia and reduced quality of life. Positive effects of tranexamic acid, an antifibrinolytic drug, have been reported on epistaxis related to this disorder. We sought to evaluate the efficacy of treating nosebleeds in hereditary hemorrhagic telangiectasia with tranexamic acid. - Materials and Methods - In a randomized, double-blind, placebo controlled, cross-over phase IIIB study, 1 gram of tranexamic acid or placebo was given orally 3 times daily for 3months for a total of 6months. - Results - 22 patients were included in the intention-to-treat analysis. Hemoglobin levels, the primary outcome measure, did not change significantly (p=0.33). The secondary outcome measure was epistaxis score and patients reported a statistically significant reduction in nosebleeds, equaling a clinically relevant 54% diminution (p=0.0031), as compared to the placebo period. No severe side effects were observed. - Conclusion - Tranexamic acid reduces epistaxis in patients with hereditary hemorrhagic telangiectasia. (Clinical trial registration numbers: BfArM 141 CHC 9008-001 and ClinicalTrials.gov NCT01031992)